Compactly Fused o‐Quinone‐Extended Tetrathiafulvalene‐o‐Quinone Triad – a Redox‐Amphoteric Ligand. Issue 21 (16th June 2014) - Chalkov, Nikolay O.; Cherkasov, Vladimir K.; Abakumov, Gleb A.; Romanenko, Galina V.; Ketkov, Sergey Yu.; Smolyaninov, Ivan V.; Starikov, Andrey G.; Kuropatov, Viacheslav A.
Abstract: A new redox‐amphoteric ligand comprising a p ‐phenylene‐extended tetrathiafulvalene (TTF) core and two o ‐quinone termini has been synthesized. This work was performed in an attempt to synthesize a bridging ligand by combining one of the most powerful organic donors with strong acceptor units in a single molecule. The product was isolated in the doubly reduced diprotonated form. An X‐ray diffraction study revealed a rigid and planar structure for this molecule. This is the first example of an air‐stable p ‐phenylene‐extended TTF with an unprotected central ring. The diquinone form itself has been prepared by oxidation of the doubly reduced diprotonated species and then characterized in solution. The electronic spectrum of this compound contains an intense peak that corresponds to intramolecular charge transfer. The spectroscopic and structural studies of both compounds were accompanied by DFT calculations. A singlet biradical ground state was predicted for the doubly reduced diprotonated form. Abstract : A fused acceptor–donor–acceptor (A–D–A) triad consisting of a π‐extended tetrathiafulvalene and sterically hindered o ‐quinones at the termini has been synthesized in a one‐pot process. The doubly reduced diprotonated form of this species has been structurally characterized. A singlet biradical ground state has been found for this form.